Developing Awareness of Environmental Assets to Improve Academic Performance Using Participatory Mapping: Membangun Kesadaran akan Aset Lingkungan untuk Meningkatkan Prestasi Akademik Menggunakan Pemetaan-berbasis Partisipasi - Depari, Catharina Dwi Astuti (Universitas Lancang Kuning, 2025)
This article was developed based on a planning program that involved undergraduate students using Participatory Asset Mapping technique at a private university in Yogyakarta. Engaging 12 students across educational programs at Universitas Atma Jaya Yogyakarta, the program aims to identify environmental assets that, according to the participants, contribute to academic performance and recommend strategies for decision-makers at the university to improve the campus environmental quality. Integrating the PAM technique, Focus Group Discussion, and structured interviews at the data collecting phase and employing Excel for data calculation and NVivo for coding at the analysis phase, the program found nine critical assets in improving academic performance along with their meaning that are defined by the functions of the assets. The recommended strategies revolved around improving the assets’ facilities, accessibility, and service quality. The findings highlight the importance of engaging students in the university’s attempts to enhance the quality of its educational services.